Water sorption on coal: effects of oxygen-containing function groups and pore structure - Liu, Ang; Liu, Shimin; Liu, Peng; Wang, Kai (International journal of coal science & technology, 2021)
Coal-water interactions have profound influences on gas extraction from coal and coal utilization. Experimental measurements on three coals using X-ray photoelectron spectroscopy (XPS), low-temperature nitrogen adsorption and dynamic water vapor sorption (DVS) were conducted. A mechanism-based isotherm model was proposed to estimate the water vapor uptake at various relative humidities, which is well validated with the DVS data. The validated isotherm model of sorption was further used to derive the isosteric heat of water vapor sorption. The specific surface area of coal pores is not the determining parameter that controls water vapor sorption at least during the primary adsorption stage. Oxidation degree dominates the primary adsorption, and which togethering with the cumulative pore volume determine the secondary adsorption. Higher temperature has limited effects on primary adsorption process.The isosteric heat of water adsorption decreases as water vapor uptake increases, which is found to be close to the latent heat of bulk water condensation at higher relative humidity. The results confirmed that the primary adsorption is controlled by the stronger bonding energy while the interaction energy between water molecules during secondary adsorption stage is relatively weak. However, the thermodynamics of coal-water interactions are complicated since the internal bonding interactions within the coal are disrupted at the same time as new bonding interactions take place within water molecules. Coal has a shrinkage/swelling colloidal structure with moisture loss/gain and it may exhibit collapse behavior with some collapses irreversible as a function of relative humidity, which further plays a significant role in determining moisture retention.